Myoglobin determination after bariatric surgery has no additional benefit - Vassilev, Georgi; Lammert, Alexander; Galata, Christian; Seyfried, Steffen; Weiß, Christel; Otto, Mirko (Bariatric surgical practice and patient care, 2019)
Aim: To analyze the value of serum myoglobin as an indicator of early acute kidney injury (AKI) after bariatric surgery.Methods: The medical records of 365 patients who underwent surgical bariatric procedures at our institution between December 2003 and December 2014 were analyzed. Preoperative creatinine, postoperative creatinine, and myoglobin levels were evaluated with regard to the occurrence of AKI following bariatric procedures. AKI is defined according to the KDIGO (Kidney Disease: Improving Global Outcomes) guideline.Results: Thirty patients (8.2%) developed AKI. Two of those patients developed AKI stage II, 1 patient AKI stage III, and 27 patients AKI stage I. AKI correlated with an elevated myoglobin levels in 28 of the 30 cases on the same day of the procedure, but only correlated with 24 of the 30 patients on the first postoperative day. Myoglobin levels were false positive in 79.8% of patients with measurements on the day of intervention and were also false-positive elevated in 65% of cases on the first postinterventional day. Hence, the determination of myoglobin levels is not superior to the determination of serum creatinine elevation for the detection of AKI after bariatric intervention.Conclusions: Measurement of serum myoglobin has no additional value for the detection of AKI after bariatric procedures compared with routine perioperative measurement of serum creatinine levels.